(untitled) (International Journal of Biology and Chemistry, 2014)
Malnutrition in low-income countries is one of the massive central issues to be solved. It means the scholars should propose effective way of solving this problem by using modern methods of breeding and harvesting. Grain legumes are regarded as principal source of vegetable protein among plants. Grain legumes are abundant by vitamins, minerals, flavonoids, and fiber, and are also convenient for cultivation in plain and alpine zones. Under arid conditions grain legumes are helpful in the exploration of the areas unsuitable for breeding to obtain steady annual harvests. This paper summarizes information on successful introduction and breeding of certain bean varieties obtained from local and foreign collections. It includes the data on biochemical comparison of different bean varieties, amino acids composition of their seeds, structural analysis and statistic data on the correlation of breeding conditions in various areas and the bean yield.